Ensino da transfilosofia sentipensante - Rodríguez, Milagros Elena (Revista Hipótese, 2023)
With a planetary decolonial transmethodical exercise - complex from comprehensive, ecosophical, and diatopic hermeneutics, we have fulfilled the complex objective of the inquiry to analyze the teaching of sentipensante transphilosophy. At the same time, we have presented epistemes of this. Surely, in traditionalism, modernist techniques and didactics would be expected to teach philosophy, but here, we have decolonized that reality precisely. Thus, in the propositional moment of the transmethod, we have that the teaching of sentipensante transphilosophy with ancestral knowledge profoundly safeguards the earth and teaches that we are nature. We decolonize the teaching of philosophy and with it philosophy itself; we strip it of its object of power, of the determinism that has drowned it in teaching, who has condemned him to perish, and it is no coincidence that in the face of cruelty, what is called philosophizing is less interested.
Keywords: Transphilosophy; Feeling; Teaching; Planetary Decoloniality; Complex